Localization of the main allergy protein in two apple cultivars grown in Sweden - Rur, Mira (2007)
Mal d 1 is an 18 kD protein and identified as a major allergen linked with pollen-associated allergies in apple. Previous studies have indicated that the amount of Mal d 1 is not only strongly dependent on apple cultivar and degree of maturity, but also has a tendency to increase during prolonged storage compared to freshly picked apples. Furthermore, it has been suggested that the most allergenic part of the apple is the peel. The aim of this study was to evaluate the use of ITP (immunotissue printing) as a method with the purpose of visualizing the localization and distribution of the main apple allergen, Mal d 1, in two apple cultivars grown in Sweden. The method includes the use of antibodies and allows for large quantities to be screened in a relatively short time compared to ILM (immunolight microscopy), which is the commonly practiced method today. In order to make a comparison, both methods were tested and evaluated. In addition, ITP was used to see if and how different storage conditions as well as cultivation methods have an effect on the content of Mal d 1. The chosen material for the study was two apple cultivars grown in Sweden: 'Aroma', known to have a relatively high content of allergen and 'Gloster', known to have a low content of allergen Comparing immunotissue prints of 'Aroma' and 'Gloster' verified the vast differences in allergen content between the two. 'Aroma' proved to have a relatively high content of allergen distributed both in peel and the pulp. In 'Gloster', the allergen content was low and was mostly concentrated to the peel and core. The highest contents of allergen were found in apples stored in normal atmosphere and the single strongest indication of Mal d 1 was found in the apple from conventional production which was harvested at the later date. Apples from organic production displayed the lowest contents of all. The experiences made from this study can confirm that ITP is a much more efficient method compared to ILM using immunogold labeling concerning time and labour intensity. Provided that my results can be confirmed with a larger material, they may help to minimize allergen levels by adjusting storage and cultivation practices. In the future, production of low-allergenic apples can help to support the organic apple farming. Suggestions for further research in this area could include using whole, transverse slices of apple, combining ITP with a more quantitative method such as ELISA of the same tissue, comparing weather data from different growing seasons, and taking more accurate data for the trees and apples analyzed in terms of e.g. nourishment and exposition to the sun etc.